The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s1063-4584(03)00089-x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Western Ontario and McMaster Universities (WOMAC) Osteoarthritis Index in Italian patients with osteoarthritis of the knee

Abstract: The Italian version of WOMAC is a reliable and valid instrument for evaluating the severity of OA of the knee, with metric properties in agreement with the original, widely used version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
178
2
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(199 citation statements)
references
References 38 publications
12
178
2
7
Order By: Relevance
“…[31][32][33][34][35][36][37] The ICC for pain, stiffness, and physical function subscales were more than 0.96, which could be considered near to totally reliable. Similar results were reported for the German, 38 Swedish, 39 and the Italian 40 languages versions.…”
supporting
confidence: 88%
“…[31][32][33][34][35][36][37] The ICC for pain, stiffness, and physical function subscales were more than 0.96, which could be considered near to totally reliable. Similar results were reported for the German, 38 Swedish, 39 and the Italian 40 languages versions.…”
supporting
confidence: 88%
“…Further, scores on the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain scale [4] are confounded by physical functioning (the scale asks about pain experienced with specific activities). Thus, WOMAC pain and physical function scores are highly correlated [41]. Together, these studies suggested the need for a new OA pain measure.…”
Section: Patient Perceptions Of Pain From Oamentioning
confidence: 89%
“…In present study WOMAC score had a direct correlation and significant difference in various K-L grades (r=0.872, P<0.001). Inoue et al [18] and Salaffi et al [20] also reported the positive correlation between WOMAC score and K-L grading. In present study Significantly higher mean sHA levels were found among the cases as compared to controls (P <0.001).…”
Section: Discussionmentioning
confidence: 90%